Self-report on the occurrence of insomnia and the habit of taking multivitamins against academic stress among students in the early period of COVID-19 pandemic - Prasetyaningtyas, Wahyu Eka; Nasri, Wa Ode Lili Andriani; Amalianita, Berru (Universitas Negeri Padang, 2020)
This study intends to determine the occurrence of insomnia and the habit of taking multivitamins against learning stress among students during the early stages of the Covid-19 pandemic. Data were obtained in two times from 308 students in East Jakarta, Indonesia, applying a descriptive quantitative approach through the Rasch Model and inferential statistics via the Bayesian Anova. The result showed that the use of multivitamins and the existence of insomnia have been proved to be linked to the incident of stress among students during the early periods of the pandemic. Although the use of multivitamins is helpful to minimize stress, students consuming this commodity are likely to experience by stress up to 40 times higher than those that experience in insomnia. This condition becomes higher assuming the students, in addition to having insomnia, are also not accustomed to receiving multivitamins. The implications of this study, including considerations for better investigation of this issue, have been discussed and concluded.